Developing English Pragmatic Based Material for Students of Hotel Management Study Program - Rahman, Benni Ichsanda; Husnaini, Husnaini (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2018)
There were some miscommunications occurred between speakers and listeners because the listener did not understand the core intent of the speaker, especially what was conveyed implies pragmatic meaning. Thus, "pragmatic" material is urgently needed to be incorporated to the curriculum of basic English as well as English conversation, to enrich student's vocabulary in understanding the culture and meanings of native English speakers. Thus, this study is aimed to develop the pragmatic based English material that is appropriate to the students’ needs of Hotel Management study program. This research was conducted based on Research and Development techniques (R & D). The research was carried out by: (1) analyzing the existing curriculum and syllabus, analyzing existing materials, and analyzing the students' needs to identify problems, (2) reviewing the principles about effective teaching materials, (3) designing syllabus and teaching materials, (4) validating new teaching materials with the experts, and (5) revising teaching materials as advised by experts. The data were collected through questionnaire analysis and interview. Meanwhile, the development of the material followed these steps, as used by Hutchinson in Ichsanda (2013: 36): 1), collected information on target needs by distributing questionnaires to students of STIM Sukma, 2) analyzed students' learning needs, 3), read and analyzed pre-existing materials; 4) developed materials according to student needs; 5), revision; 6); prepared the drafts; 7), and had a triangulation with experts; 8); final drafts; 9), product application. Based on the analysis, material that is appropriate with hotel management study program has been created and developed.Keywords: Developing materials, hotel Management